Fiber spinning process for applying metal nanoparticles to polymer devices

By using laser ablation in polymer materials, non-ionic silver nanoparticles and coral-shaped metal nanoparticles prepared, forming fiber-spinning materials with antimicrobial and UV protection functions, solving the lack of antimicrobial properties of polymer materials in medical applications. and the problem of UV damage, achieving efficient protection effect over a long period of time.

CN119213175APending Publication Date: 2024-12-27EWOK NANO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380040206.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-19
Filing Date
2023-04-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing polymer materials have insufficient antimicrobial properties in medical applications, especially poor protection against antibiotic-resistant bacteria, and are susceptible to damage to UV radiation, resulting in the failure of the product during use.

Method used

Using polymer compositions incorporated with metal nanoparticles, non-ionic silver nanoparticles and coral-shaped metal nanoparticles prepared by laser ablation, forming fiber spinning materials with antimicrobial and UV protection functions to ensure that nanoparticles are in the polymer No metal ions are released in the process, avoid resistance problems, and reduce UV damage through wavelength shift technology.

Benefits of technology

It achieves effective antimicrobial and UV protection effects over a long period of time, avoids resistance problems of conventional silver nanoparticles and UV damage to polymer materials, extends the service life of the product and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005131892230000011
    Figure HDA0005131892230000011
  • Figure HDA0005131892230000021
    Figure HDA0005131892230000021
  • Figure HDA0005131892230000022
    Figure HDA0005131892230000022
Patent Text Reader

Abstract

Polymer fibers incorporating metal nanoparticles and medical devices made therefrom are disclosed. The disclosed polymer fibers can be used to form medical devices, including implantable medical devices, having effective antimicrobial properties. The disclosed polymer fibers incorporate metal nanoparticles that function without releasing metal (e.g., silver) ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to polymer compositions containing antimicrobial nanoparticles, devices formed from the polymer compositions, and fiber spinning manufacturing methods for forming such polymer compositions and devices. Background Art

[0002] Polymers used in medical and other applications are generally inexpensive and can be used for many different functions. Polymer fabrications can be made using injection molding methods. One problem with injection molding polymers is that the surface finish of the product can be spongy, with pores that can extend several microns deep into the product. For example, Figure 1 is a scanning transmission electron microscope (STEM) image of the surface of polystyrene from hot extruded particles. The polymer surface is highly porous, making it possible to accommodate bacteria and other microorganisms. The growth of such microorganisms can be a cause of concern for hospitals and other institutions in the medical field. The management of polymers used in highly sensitive areas (including many medical applications) requires expensive and rigorous sterilization and storage procedures. Despite this, it is known that deteriorated tissues and infections are caused by the use of damaged polymers used to deliver substances to patients and / or implanted in patients. Drug-resistant microbial infections can also be caused by the use of damaged polymer products, resulting in expensive healthcare maintenance and even death.

[0003] Overuse of antibiotics has in some cases led to antibiotic resistant bacteria and other treatment resistant microbes. There is concern that increased resistance to antibiotics may result in microorganisms that cannot be treated with conventional techniques. Currently, there are few methods for sterilization and microbial control that do not require the use of conventional antibiotics. In some cases, medical devices containing antibiotics do not prevent biofilm formation and / or do not prevent infection with bacteria that are resistant to antibiotics. In such cases, the use of antibiotics in polymeric materials does not protect patients from infection and may even give people a false sense of security.

[0004] Attempts have been made to incorporate ionic colloidal silver and silver nanoparticles into polymeric materials to impart antimicrobial activity to polymers. However, colloidal silver (i.e., silver nanoparticles made by conventional chemical reduction methods, which silver nanoparticles typically have some form of capping agent) and ionic silver have now been found to have antimicrobial resistance. McNeilly et al., “Emerging Concern for Silver Nanoparticle Resistance in Acinetobacter baumannii and Other Bacteria,” Front. Microbiol., April 16, 2021, discusses the emergence of multiple antibiotic-resistant bacteria, including Acinetobacter baumannii, Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. Among them, A. baumannii is of particular concern and has been found to have developed resistance to colloidal silver nanoparticles, as have Escherichia coli, Enterobacter cloacae, and Enterobacter spp. cloacae), S. typhimurium, B. subtilis, S. aureus, Pseudomonas aeruginosa, K. pneumoniae, Serratia marcescens, and Acinetobacter spp.

[0005] Silver, “Bacterial silver resistance: molecular biology and uses and misuses of silver compounds,” FEMS Microbiology Reviews, Vol. 27, No. 2-3, June 2003, pp. 341–35, discusses silver resistance in Salmonella and E. coli. Elkrewi, et al., “Cryptic silver resistance is prevalent and readily activated in certain Gram-negative pathogens,” J. Antimicrob. Chemother., Nov. 1, 2017; 72(11): 3043-3046 discloses resistance of Gram-negative pathogens (e.g., Enterobacter spp., Klebsiella spp., E. coli, Pseudomonas aeruginosa, Acinetobacter spp., Citrobacter spp., and Proteus spp.) to colloidal silver nanoparticles. Hosney, “The increasing threat of silver-resistance in clinical isolates from wounds and burns,” Infect Drug Resist. 2019;12:1985–2001 discusses colloidal silver-resistant Klebsiella pneumoniae, Staphylococcus aureus, Escherichia coli, Enterobacter cloacae, Pseudomonas aeruginosa, and Acinetobacter baumannii. Percival, et al., “Bacterial resistance to silver in wound care,” J. Hospital Infection, Vol. 60, No. 1, May 2005, pp. 1-7, discuss the concerns and potential for colloidal silver-resistant microorganisms in wounds. et al., “Consequences Of Long-Term Bacteria's Exposure To Silver Nanoformulations With Different PhysicoChemical Properties,” Intl. J. of Nanomedicine, 2020: 15 199–213, discuss colloidal silver resistance in Gram-positive and Gram-negative bacteria.

[0006] An article titled “Are Silver Nanoparticles a Silver Bullet Against Microbes?” July 13, 2021, https: / / news.engineering.pitt.edu / are-silver-nanoparticles-a-silver-bu llet-against-microbes / (accessed October 12, 2022) discusses colloidal silver nanoparticle-resistant E. coli, stating: “At first, the bacteria could only survive low concentrations of silver nanoparticles, but as the experiments continued, we found that they could survive higher doses… Interestingly, we found that the bacteria became resistant to the silver nanoparticles, but not just the silver ions they released.” The team sequenced the genome of E. coli exposed to silver nanoparticles and found mutations in a gene that corresponds to an efflux pump that pushes heavy metal ions out of the cell. “It’s possible that some form of silver is entering the cell, and when it arrives, the cell mutates to rapidly pump the silver out… More work is needed to determine if researchers can overcome this resistance mechanism through particle design.”

[0007] Silver nanoparticles prepared by conventional chemical synthesis methods have external bond angles and edges where silver ions can be released, even though most of the nanoparticles are in the ground state. Adding ion-releasing metal nanoparticles to polymers produces nanoparticle-impregnated polymers and plastics that are sources of unwanted metal ions (such as silver ions) that can be toxic to human and animal tissues under excessive exposure. In addition, the release of ions may decrease over time. Therefore, even if there is a beneficial antimicrobial effect associated with silver ion release, this effect will decrease over time because the ions will be leached out of the bulk polymer material. In cases where silver ion release is the primary method of antimicrobial action (which is the case with conventional colloidal silver products), the antimicrobial activity of the polymer will likewise decrease over time.

[0008] In addition, exposure to solar radiation can cause weakening and other structural damage to polymers. When UV energy is absorbed by polymers, the UV energy may excite electrons, creating free radicals that can cause degradation of the plastic. Polymers affected by UV radiation may appear chalky, the surface of the polymer may become brittle, and noticeable color changes may appear on the surface of the polymer. UV-induced degradation may cause cracks in polymer products and may cause the product to fail completely. For example, UV radiation irradiated on polypropylene and / or low-density polyethylene can interact with tertiary carbon bonds in their structure, which can then interact with oxygen in the atmosphere. This can create carbonyl groups in the backbone of the structure, making the plastic product susceptible to cracking or discoloration.

[0009] Ultraviolet B radiation ("UVB radiation") is generally considered to be in the wavelength range of about 280 to about 315 nanometers. Ultraviolet A radiation ("UVA radiation") is generally considered to be in the wavelength range of about 315 to about 400 nanometers. Ultraviolet C radiation (UVC) is generally considered to be in the wavelength range of about 100 to about 280 nanometers.

[0010] In view of the foregoing, there remains a need to find improved polymeric materials that exhibit effective antimicrobial properties and that can be effectively used in medical devices, including implantable medical devices. Summary of the invention

[0011] Disclosed are polymer compositions incorporating metal nanoparticles, medical devices made from the polymer compositions, and fiber spinning methods for forming such polymer compositions and devices. The disclosed polymer compositions can be used to form medical devices (including implantable medical devices) with effective antimicrobial properties. The disclosed polymer compositions incorporate metal nanoparticles that work without releasing metal (e.g., silver) ions. When exposed to sunlight and / or other UV light sources, the disclosed polymer material can also effectively resist UV damage.

[0012] In some embodiments, the disclosed polymer compositions include wavelength-shifting metal nanoparticles for protecting exposed surfaces from UV radiation. For example, the polymer compositions can downconvert incident UV light into longer wavelength light that is less damaging or non-damaging to polymer linkages.

[0013] The disclosed polymer compositions containing metal nanoparticles also have antimicrobial properties to prevent microbial colonization thereon (including preventing microbial colonization within the pores of polymeric materials and structures formed by polymeric materials). Such nanoparticle-modified polymers are not prone to developing silver nanoparticle antibiotic resistance, which is often the case with conventional colloidal silver prepared by chemical synthesis. Surprisingly and unexpectedly, it has been found that non-ionic silver nanoparticles formed by laser ablation do not result in silver nanoparticle resistance, at least not to the same extent as when conventional colloidal silver or silver nanoparticles prepared by chemical synthesis are used, which are known to release silver ions as the primary mode of their antimicrobial activity.

[0014] Metal (e.g., silver) nanoparticles produced by laser ablation methods (and having a smooth spherical morphology and a narrow size distribution) can be added to polymers to reduce colonization by bacteria or other microorganisms. Unexpectedly, spherical silver nanoparticles made by laser ablation and having a narrow particle size distribution did not result in the same degree of microbial resistance as conventional colloidal silver or silver nanoparticles formed by chemical synthesis.

[0015] In some embodiments, the spherical metal (e.g., silver) nanoparticles have an average diameter and a particle size distribution, wherein at least 99% of the spherical metal nanoparticles have a particle size within 30% of the average diameter, or within 20% of the average diameter, or within 10% of the average diameter and / or wherein at least 99% of the spherical metal nanoparticles have a diameter within ±3 nm of the average diameter, or within ±2 nm of the average diameter, or within ±1 nm of the average diameter.

[0016] In some embodiments, the composition may include coral-shaped metal nanoparticles as an alternative or in addition to spherical metal nanoparticles or spherical metal nanoparticles.Coral-shaped metal (e.g., gold) nanoparticles have an uneven cross-section and a spherical structure formed by multiple nonlinear chains connected together without right angles.

[0017] In some embodiments, the metal nanoparticles may include spherical metal (e.g., silver) nanoparticles and / or coral-shaped metal (e.g., gold) nanoparticles. In some embodiments, coral-shaped metal nanoparticles may be used together with spherical metal nanoparticles. Coral-shaped nanoparticles may beneficially enhance spherical metal nanoparticles.

[0018] In some embodiments, the metal nanoparticles may include at least one metal selected from the group consisting of silver, gold, platinum, palladium, rhodium, osmium, ruthenium, rhenium, molybdenum, copper, iron, nickel, tin, beryllium, cobalt, antimony, chromium, manganese, zirconium, tin, zinc, tungsten, titanium, vanadium, lanthanum, cerium, heterogeneous mixtures thereof, and alloys thereof. Nanoparticles consisting of silver, gold, mixtures, and alloys thereof may be particularly effective.

[0019] In some embodiments, the polymer composition can be made from a liquid polymer composition into which metal nanoparticles are incorporated, for example by mixing the metal nanoparticles in an uncured polymer solution or polymer melt and drawing polymer fibers therefrom using electrospinning or wet spinning methods. The metal nanoparticles are mixed throughout the formed polymer fibers.

[0020] Some of the metal nanoparticles on the surface of the polymer material and / or embedded in the pores will provide antimicrobial activity to prevent microorganisms from growing on the polymer material. The metal nanoparticles will also protect the polymer material from damage by UV radiation by downconverting the incident UV energy into lower energy wavelengths that are less harmful or non-damaging to the polymer material.

[0021] The polymer compositions disclosed herein can advantageously provide antimicrobial and UV protection effects over extended periods of time, even without depletion of the nanoparticles after wear or processing. For example, because the embedded nanoparticles do not rely on ion release as the primary means of antimicrobial activity, the polymer compositions disclosed herein can provide this function for a longer period of time than similar polymer compositions utilizing conventional nanoparticles formed by chemical synthesis.

[0022] This Summary is provided to introduce a selection of concepts in a simplified form that are further described below in the Detailed Description. This Summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to serve as an indication of the scope of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Various objects, features, characteristics and advantages of the present invention will become apparent and more readily understood from the following description of the embodiments, taken in conjunction with the accompanying drawings and the appended claims, all of which constitute a part of this specification. In the accompanying drawings, the same reference numerals may be used to indicate corresponding or similar parts in the various drawings, and the various elements depicted are not necessarily drawn to scale, wherein:

[0024] Figure 1 is a scanning transmission electron microscopy image of the polystyrene surface from hot extruded pellets;

[0025] Figure 2A-2C A thermoplastic containing Ag nanoparticles is shown;

[0026] Figure 3A -B schematically shows a microorganism after absorbing spherical metal nanoparticles from a matrix and the disulfide bonds are catalytically denatured by the spherical nanoparticles;

[0027] Figure 4 STEM image showing Ag nanoparticles inside MRSA SA62 resistant bacteria;

[0028] Figures 5A-5C shows a STEM image of Tecoflex EG-93A-B20 thermoplastic impregnated with nanoparticles;

[0029] Figures 6A-6C shows a STEM image of Isoplast 2510 thermoplastic impregnated with nanoparticles;

[0030] Figure 7A-7B shows a close-up STEM image of Ag nanoparticles embedded in a thermoplastic;

[0031] Figures 8A-8B Schematic diagrams showing example electrospinning and wet spinning methods, respectively; and

[0032] Fig. 9 is a rendering of nanoparticles embedded in electrospun fibers. DETAILED DESCRIPTION

[0033] I. Introduction

[0034] The term "nanoparticle" generally refers to a particle with a maximum dimension less than 100 nm. Regardless of size, bulk materials generally have constant physical properties, but at the nanometer scale, size-dependent properties are often observed. Therefore, when the size of the material approaches the nanometer scale, and when the percentage of atoms on the surface of the material becomes significant, the properties of the material change. For bulk materials greater than 1 micron (or micron), the percentage of atoms on the surface is negligible relative to the number of atoms in the bulk of the material. Therefore, the interesting and sometimes unexpected properties of nanoparticles are largely due to the large surface area of ​​the material, which dominates the contribution made by relatively small bulk materials.

[0035] The polymer compositions disclosed herein can be made from a liquid polymer composition into which metal nanoparticles are incorporated, for example by mixing the metal nanoparticles in an unsolidified polymer solution or polymer melt and drawing polymer fibers therefrom using electrospinning or wet spinning methods. The metal nanoparticles are mixed throughout the formed polymer fibers.

[0036] As used herein, "polymer composition" refers to the polymer fiber product obtained by the disclosed electrospinning or wet spinning process, and can be used synonymously with terms such as "polymer fiber" and similar terms. "Polymer solution" or "polymer melt" refers to a liquid and / or uncured composition before being drawn into fibers by one of the aforementioned methods. A "polymer solution" can be an uncured solution containing monomers and / or oligomers, which undergoes polymerization and / or crosslinking when drawn into fibers, while a "polymer melt" can be a polymer that is heated to melt and re-cured when drawn into fibers.

[0037] Where some examples may refer to polymer solutions and other examples may refer to polymer melts, it should be understood that the same principles apply to either embodiment. As disclosed herein, metal nanoparticles may be mixed with a polymer solution or polymer melt prior to a fiber spinning process such that the resulting polymer composition contains metal nanoparticles.

[0038] Examples of polymer compositions that can be used in the disclosed embodiments include silicone, polysiloxane, epoxy resin, polystyrene (PS), polyethylene (PE) (including low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and high-density polyethylene (HDPE)), polypropylene (PP), ethylene-vinyl acetate copolymer (EVA), polycarbonate (PC), polyurethane (PU), polyetheretherketone (PEEK), polylactic acid (PLA), polyhydroxyalkanoate (PHA), polyester (PES), polyethylene terephthalate (PET), polyethylene glycol (PES), polyethylene terephthalate (PEEK), polyethylene glycol (PEEK), polyethylene terephthalate (PEEK), polyethylene terephthalate (PES), polyethylene terephthalate (PEEK ... Polyethylene glycol ester (PET), polymethyl methacrylate (PMMA), polybutylene terephthalate (PBT), phenolic resin (PF), nylon / polyimide (PA), melamine formaldehyde (MF), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), polyvinyl pyrrolidone (PVP), acrylonitrile butadiene styrene terpolymer (ABS), styrene block copolymer (SBC), rubber latex (natural or synthetic), nitrile (such as nitrile rubber (NBR)), medical grade thermoplastic elastomer (TPE), aramid (such as Kevlar), carbon fiber reinforced polymer and combinations thereof.

[0039] II. Nanoparticles

[0040] The metal nanoparticles used in the disclosed polymer compositions can be non-ionic, ground state, and have no external edges or bond angles that result in the release of metal ions. Spherical metal nanoparticles are typically used to kill microorganisms, although coralline metal nanoparticles are often used in conjunction with spherical metal nanoparticles to provide antimicrobial activity.

[0041] In some embodiments, the metal nanoparticles may include or consist essentially of non-ionic ground state metal nanoparticles without external edges or bond angles that result in the release of metal ions. Embodiments include spherical metal nanoparticles, coral-shaped metal nanoparticles, and mixtures of spherical metal nanoparticles and coral-shaped metal nanoparticles.

[0042] Conventional silver nanoparticles made by chemical reduction (usually involving a capping agent) tend to exhibit clustered, crystalline, polyhedral or polyhedral-like shapes rather than true spheres with rounded and smooth surfaces. Such nanoparticles often aggregate together and have a relatively wide size distribution. In some cases, conventional silver nanoparticles are formed as a silver shell formed on a non-metallic seed material.

[0043] In contrast, spherical nanoparticles that may be included in the polymer compositions disclosed herein may exhibit one or more of the following: (1) solid metal form, (2) substantially no aggregation, (3) exposed / uncoated surface, (4) smooth surface morphology, and / or (5) narrow size distribution. As used herein, an "exposed" or "uncoated" surface is a surface that omits the capping agent and directly exposes the metal surface to the environment.

[0044] The metal nanoparticles of the disclosed polymer composition, including spherical and coral-shaped nanoparticles, can contain any desired metal, metal mixture or metal alloy, including at least one of silver, gold, platinum, palladium, rhodium, osmium, ruthenium, rhenium, molybdenum, copper, iron, nickel, tin, beryllium, cobalt, antimony, chromium, manganese, zirconium, tin, zinc, tungsten, titanium, vanadium, lanthanum, cerium, heterogeneous mixtures thereof or alloys thereof. Nanoparticles composed of silver, gold and mixtures and alloys thereof can be particularly effective.

[0045] In some embodiments, gold (Au) nanoparticles are included in the polymer composition and used to down-convert incident UV radiation. The gold nanoparticles can down-convert light waves into longer wavelengths of light with lower energy and harmfulness. The gold nanoparticles can down-convert light wavelengths to the red region of the spectrum. In some embodiments, the gold nanoparticles are spherical. In some embodiments, the diameter of the gold nanoparticles is about 1 to 40 nm.

[0046] The nanoparticle composition can include spherical metal nanoparticles, coralline metal nanoparticles, or a combination of the two. Spherical metal nanoparticles generally have stronger antimicrobial activity, although coralline metal nanoparticles can also provide antimicrobial activity and the antimicrobial activity of spherical metal nanoparticles can be enhanced when the two are combined.

[0047] According to the disclosures of U.S. Pat. No. 9,849,512, U.S. Pat. No. 10,137,503 and No. 10,610,934, nonionic ground state spherical metal nanoparticles without external edges or bond angles and compositions containing such nanoparticles can be prepared. According to the disclosure of U.S. Pat. No. 9,919,363, nonionic ground state coralline metal nanoparticles without external edges or bond angles and compositions containing such nanoparticles can be prepared. Compositions containing a mixture of spherical metal nanoparticles and coralline metal nanoparticles are disclosed in U.S. Pat. No. 9,434,006. Each of the foregoing patents is incorporated herein by reference in its entirety.

[0048] The liquid medium (e.g., a polymer solution or a polymer melt) in which the nanoparticles are mixed can include nanoparticles at a concentration of about 50 ppb to about 100 ppm, or about 100 ppb to about 50 ppm, or about 200 ppb to about 20 ppm, or about 400 ppb to about 10 ppm, or about 600 ppb to about 6 ppm, or about 800 ppb to about 4 ppm, or about 1 ppm to 3 ppm, or about 2 ppm, or a range using any combination of the foregoing values ​​as endpoints (based on the weight of the liquid medium applied to the polymer composition).

[0049] Nanoparticles can be incorporated into polymers by known methods (e.g., methods disclosed in U.S. Application No. 17 / 969,299 and U.S. Application No. 17 / 970,172,172, which are incorporated herein by reference). In some embodiments, polymer compositions can be made of thermoplastic materials into which metal nanoparticles are incorporated, such as by coating polymer beads or particles, which are then thermoplastically formed into the desired structure of the finished product. In other embodiments, polymer compositions can be made of two-part compositions, in which metal nanoparticles are included in one or both parts of the composition. In both cases, the metal nanoparticles are mixed throughout the polymer composition, either in a molten state before molding and cooling, or in a liquid state before molding and thermal curing. Nanoparticles can be added to monomers or oligomers to form desired polymers or copolymers. Nanoparticles can be applied to spinning polymer fibers through a coagulation bath containing nanoparticles.

[0050] After the nanoparticles are incorporated into the polymer composition (e.g., into formed fibers), the nanoparticles can be included in a range from about 0.5 mg / kg to about 8 mg / kg, for example, about 1 mg / kg, 2 mg / kg, 3 mg / kg, 4 mg / kg, 5 mg / kg, 6 mg / kg, 7 mg / kg, or any combination of the foregoing values ​​as endpoints.

[0051] Spherical metal nanoparticles can have an average particle size (i.e., diameter) in the range of about 1nm to about 20nm, such as about 3nm to about 14nm, or about 4nm to about 13nm, or about 5nm to about 12nm, or about 6nm to about 10nm. In some embodiments, spherical metal nanoparticles can have a diameter of about 40nm or less, about 35nm or less, about 30nm or less, about 25nm or less, about 20nm or less, about 15nm or less, about 10nm or less, about 7.5nm or less, or about 5nm or less. The composition can include nanoparticles whose concentration range endpoints are defined by any two of the aforementioned values.

[0052] As used herein, unless otherwise indicated, average diameter (i.e., average particle size) refers to the number-average diameter, which can be determined according to standard methods known in the art. For example, the average diameter can be determined by microscopy (e.g., scanning transmission electron microscopy (STEM)) and analysis of the resulting image. Another suitable method for determining the average diameter of a group of metal nanoparticles is dynamic light scattering (DLS), which is usually reported on a volume basis.

[0053] The spherical metal nanoparticles may have a particle size distribution wherein at least 99% of the metal nanoparticles have a particle size within 30% of the average diameter, or within 20% of the average diameter, or within 10% of the average diameter, and / or wherein at least 99% of the spherical nanoparticles have a diameter within ±3 nm of the average diameter, or within ±2 nm of the average diameter, or within ±1 nm of the average diameter. The spherical nanoparticles may have a zeta potential of at least about ±10 mV (absolute value), or at least about ±15 mV, or at least about ±20 mV, or at least about ±25 mV, or at least about ±30 mV.

[0054] In some embodiments, coral-shaped metal nanoparticles can be used in combination with spherical metal nanoparticles. Generally speaking, spherical metal nanoparticles can be smaller than coral-shaped metal nanoparticles, and in this way can provide very high surface area for catalyzing desired reactions or provide other desired benefits. On the other hand, compared to spherical nanoparticles, the generally larger coral-shaped nanoparticles can exhibit a higher surface area per unit mass because the coral-shaped nanoparticles have internal space and surface, rather than a solid core and only an external surface.

[0055] In at least some cases, providing a nanoparticle composition containing both spherical and coral-shaped nanoparticles can provide synergistic results. In addition to providing its own unique benefits, coral-shaped nanoparticles can also help carry and / or enhance the activity of spherical nanoparticles. For example, smaller particles can provide relatively better anti-UVB radiation protection, while relatively larger particles can provide better anti-UVA radiation protection. In some embodiments, the combination of spherical and coral-shaped nanoparticles can result in synergistic broad-spectrum protection, with a greater amount of protection (e.g., the amount of reflected UV radiation) per unit amount of active ingredient relative to a single size and / or single shape composition.

[0056] In some embodiments, the mass ratio of spherical nanoparticles to coralline-shaped nanoparticles in the nanoparticle composition may be in the range of about 1:1 to about 50:1, or about 2.5:1 to about 25:1, or about 5:1 to about 20:1, or about 7.5:1 to about 15:1, or about 9:1 to about 11:1, or about 10: 1. The particle number ratio of spherical nanoparticles to coralline-shaped nanoparticles in the nanoparticle composition may be in the range of about 10:1 to about 500:1, or about 25:1 to about 250:1, or about 50:1 to about 200:1, or about 75:1 to about 150:1, or about 90:1 to about 110:1, or about 100:1.

[0057] In some embodiments, at least a portion of the metal nanoparticles are selected to selectively reflect, block and / or scatter a specific range of solar radiation. For example, a first group of metal nanoparticles can be selected to be spherical metal nanoparticles with a smaller relative size, so that they selectively reflect, scatter and / or block more specific UVB radiation, while a second group of metal nanoparticles can be selected to be coral-shaped metal nanoparticles with a larger relative size, so that they selectively reflect, scatter and / or block more specific UVA radiation.

[0058] In some embodiments, the polymer composition includes at least one spherical antimicrobial nanoparticle component and a larger coralline nanoparticle component.

[0059] III. Antimicrobial Function of Nanoparticles

[0060] Figure 2A-2C is a STEM image showing a thermoplastic containing silver (Ag) nanoparticles 1, which provide antimicrobial and / or wavelength shifting properties to the polymer composition.

[0061] Figure 3A-3B Schematic diagram of microorganisms after absorbing spherical metal nanoparticles from a substrate and the disulfide bonds being catalyzed and denatured by the spherical nanoparticles. Figure 3ASchematically shown is a microorganism 608 that has absorbed spherical nanoparticles 604 from a solid substrate 602, such as by active absorption or other transport mechanisms. Optionally, the spherical nanoparticles 604 can be provided in a composition (not shown), such as in a liquid or gel carrier. The nanoparticles 604 can move freely throughout the interior 606 of the microorganism 608 and come into contact with one or more important proteins or enzymes 610, which, if denatured, will kill or disable the microorganism.

[0062] One way in which nanoparticles might kill or denature microorganisms is by catalyzing the cleavage of disulfide (SS) bonds in important proteins or enzymes. Figure 3B Schematically shows a microbial protein or enzyme 710 with disulfide bonds being catalytically denatured by adjacent spherical nanoparticles 704 to produce a denatured protein or enzyme 712. In the presence of bacteria or fungi, the cleavage of disulfide bonds and / or the cleavage of other chemical bonds of important proteins or enzymes may occur inside the cell, thereby killing the microorganism in this way. This catalytic cleavage of disulfide (SS) bonds is facilitated by the generally simple protein structure of microorganisms, in which many important disulfide bonds are exposed and easily catalytically cleaved.

[0063] Another potential mechanism by which metal (eg, silver) nanoparticles can kill microorganisms is through the production of reactive oxygen species (eg, peroxides), which can oxidatively break protein bonds, including but not limited to amide bonds.

[0064] Although nonionic metal nanoparticles are lethal relative to microorganisms, they have been shown to be harmless and nontoxic to humans, mammals, and animals, which, compared to simple microorganisms, contain more complex protein structures in which most or all of the important disulfide bonds are shielded by other more stable regions of the protein. In many cases, nonionic nanoparticles do not interact with or attach to human cells, other mammalian cells, or other animal cells, and are rapidly and safely excreted in the urine without damaging the kidneys or other cells, tissues, or organs.

[0065] The interaction of silver (Ag) nanoparticles within microorganisms has been shown to be particularly lethal in the presence of spherical silver (Ag) nanoparticles, rather than relying on silver ions (Ag + ) to provide the desired antimicrobial effect, which is typical of conventional colloidal silver compositions. Silver (Ag) nanoparticles are able to provide effective microbial control without releasing any significant or actual toxic silver ions (Ag) into the patient or the surrounding environment. +), which is a significant advance in the art. Any amount or concentration of silver ions released by silver nanoparticles, if any, is far below the known or inherent toxicity levels for animals such as mammals, birds, reptiles, fish, and amphibians.

[0066] Figure 4 STEM images of silver (Ag) nanoparticles inside MRSA SA62 drug-resistant bacteria are shown. The STEM images coupled with electron diffraction spectra provide evidence of disruption of disulfide bonds and sites of ferredoxin.

[0067] The use of non-ionic silver nanoparticles prepared using laser ablation provides advantages over conventional silver nanoparticles, which are known to work primarily by releasing silver ions and which have been shown to cause antimicrobial silver nanoparticle resistance. As mentioned above, conventional silver nanoparticles prepared using chemical reduction methods are known to cause antimicrobial resistance, meaning that their effectiveness in killing microorganisms decreases over time. Some studies have shown that microorganisms become resistant to ionic silver in as few as 6 generations.

[0068] In contrast, spherical nanoparticles that may be included in the polymer compositions disclosed herein have been shown to have stable antimicrobial activity, with no decrease in antimicrobial activity, including no significant decrease in MIC (minimum inhibitory concentration), even after 28 passages / generations.

[0069] IV. UV protection function of nanoparticles

[0070] Metal nanomaterials of the type disclosed herein and having a diameter or size in the range of about 10nm to 40nm have a loose dielectric field. When a large number of particles are gathered together, the dielectric effect on the light waves passing through will not be weakened, but can be frequency-shifted to the red end or blue end of the electromagnetic spectrum. A polymer composition with enough such nanoparticles can affect UV rays and move them to the red end of the spectrum, thereby reducing the entry of photon energy at a level that reduces overall damage.

[0071] In some embodiments, polymer compositions can include metal nanoparticles with a high refractive index to reflect and / or scatter incident UV radiation. For example, the refractive index of the nanoparticles used in polymer compositions of the present disclosure for UVA and / or UVB radiation can be from about 1.5 to about 4.6, or from about 2.0 to about 4.0, or from about 2.5 to about 3.5. In some embodiments, the refractive index of the nanoparticles for UVB radiation will be higher (for example, the refractive index increases as the wavelength decreases) relative to UVA radiation. However, in other embodiments, the refractive index of the nanoparticles will be lower (for example, the refractive index increases as the wavelength increases) for UVB radiation relative to UVA radiation.

[0072] In some embodiments, the polymer composition may include nanoparticles having photostability such that upon exposure to solar radiation (e.g., in an environment having a relatively high UV index of about 15), the nanoparticles do not degrade or lose effectiveness in protecting against UV radiation (e.g., remain about 100% effective, or remain about 95-100% effective, or about 90-100% effective, or about 80-100% effective) for at least a given period of time (e.g., about 1 hour, or about 2-4 hours, or about 4-6 hours, about 6-12 hours or longer, or even indefinitely).

[0073] In some embodiments, the polymer composition exhibits radiation protection properties. For example, some embodiments include a plurality of nanoparticles (e.g., beryllium and / or gold) configured to absorb harmful radiation (e.g., alpha particles, beta particles, and / or gamma radiation), thereby reducing or eliminating the amount of radiation that passes through the nanoparticle-treated material.

[0074] In some embodiments, the gold nanoparticles dispersed throughout the polymer composition downconvert incident UV radiation to less harmful UV radiation. In some embodiments, the gold nanoparticles can shift the incident UV radiation down by at least about 50 nm, or at least about 100 nm, or at least about 150 nm, such as about 200 nm. In some embodiments, the gold nanoparticles can shift the incident UV radiation down from UV light to visible light. In some embodiments, the gold nanoparticles can shift the incident UV radiation down from UV wavelengths to red and / or green wavelengths.

[0075] In some embodiments, gold nanoparticles dispersed throughout the polymer composition can absorb high energy incident UV radiation and emit lower energy wavelengths, thereby imparting UV protection to the polymer composition and products made therefrom. Unexpectedly, the ability of the gold nanoparticles to permanently perform this wavelength / radiation energy downshift does not show degradation with use. That is, the gold nanoparticles retain their UV protection capabilities and are not significantly degraded by incident UV radiation. This beneficially prolongs the effectiveness of the polymer composition and products made therefrom. This also means that lower concentrations of gold nanoparticles or other wavelength-shifted metal nanoparticles can be used, thereby reducing production costs while maintaining product integrity.

[0076] V. Fiber Spinning Polymer Compositions with Nanoparticles

[0077] a. Electrospinning

[0078] Electrospinning methods are particularly suitable for making polymer microfibers and polymer nanofibers. These fibers can then be applied to or incorporated into a variety of devices and surfaces. Many medical devices can be made using electrospun fibers.

[0079] Fig. 8A is a schematic diagram of an example electrospinning system 100. Electrospun fibers are produced by applying a sufficiently high voltage between a tip 102 and a collector 104. A polymer solution / melt 106 is contained within the tip 102. The application of the voltage charges the polymer solution / melt 106. Electrostatic repulsion counteracts surface tension to stretch the droplet. At a critical point, a charged liquid jet is formed toward the collector 104.

[0080] The charged liquid jet can be elongated by a whipping process caused by electrostatic repulsion induced at small bends in the fiber. The fiber is ultimately deposited on and collected by the collector 104. The illustrated system 100 includes a rotating collector 104. Other embodiments may additionally or alternatively include other types of collectors, such as a planar collector.

[0081] The elongation and thinning of the fibers caused by bending instability results in the formation of uniform fibers with diameters as low as nanometers. Various solution parameters such as viscosity, polymer concentration, molecular weight, conductivity, and / or surface tension play a role in the size and shape of the resulting fibers. Additional parameters may include voltage, tip to collector distance, feed rate, humidity, temperature, collector motion and size, and / or tip 102 specifications.

[0082] By mixing the metal nanoparticles with the polymer solution / melt 106, the resulting fibers incorporate the metal nanoparticles throughout the bulk of the fibers and on the surfaces of the fibers.

[0083] b. Wet (Hydro) spinning

[0084] Another manufacturing method for plastics, polymers and fibers is wet spinning (also known as hydrospinning). Similar to electrospinning, the wet spinning method is particularly suitable for making polymer microfibers and polymer nanofibers. These fibers can then be applied to or incorporated into various devices and surfaces.

[0085] Figure 8B 200 is a schematic diagram of an exemplary wet spinning system 200. Wet-spun fibers are produced by injecting a polymer solution / melt 206 from a container 202 into a coagulation bath 208 (typically water). When the polymer solution / melt 206 is injected or extruded into the bath 208, the injected stream will begin to precipitate to form fibers. The fibers can be spun or wound around a collector 204 (e.g., a rotating collector). A spinner or other suitable instrument can be used to inject (or extrude) the polymer solution / melt 206 into the bath 208.

[0086] By mixing the metal nanoparticles with the polymer solution / melt 206, the resulting fibers incorporate the metal nanoparticles throughout the fiber bulk and on the fiber surface. The nanoparticles may also be applied to the spun fibers via a coagulation bath 208.

[0087] c. Example polymer solution / melt

[0088] Various polymers can be used as polymer solutions / melts in electrospinning or wet spinning methods, including any polymer compositions disclosed elsewhere herein or their mixtures. Selected polymers can depend on the desired properties of the resulting fiber and the final application of the fiber. Industrial polymers, biodegradable polymers, specialty polymers and natural polymers are all suitable raw materials. Polymer matrix nanofiber composites can be produced using electrospinning with electrospinnable polymers. Polymer solutions / melts can include resins and / or epoxy resins or resins and / or epoxy resins can be used as raw materials.

[0089] Prior to the fiber spinning process, one or more fillers may be mixed with the polymer solution / melt. Fillers may include, but are not limited to, metal oxide nanoparticles (e.g., in addition to the metal nanoparticles disclosed herein), therapeutic agents, or combinations thereof. Therapeutic agents may include, but are not limited to, nonsteroidal anti-inflammatory drugs (NSAIDs) and other anti-inflammatory drugs, antibiotics, pulmonary medications, antiallergic drugs, antihistamines, vasodilators, muscle relaxants, steroids, antifungal agents, bronchodilators, nitroglycerin, cough suppressants, and / or other suitable therapeutic agents. The therapeutic agent incorporated into the polymer solution / melt will depend on the final application of the resulting fiber (e.g., configuration on an implantable medical device) and / or the specific condition to be treated (e.g., allergies, bacterial infections, etc.).

[0090] VI. Medical Devices

[0091] The polymer composition manufactured using one or more methods disclosed herein can include medical devices. The medical devices formed in this way are beneficially protected from UV radiation and microbial growth. The metal nanoparticles incorporated into the medical device can downconvert the incident UV radiation into radiation of lower energy. This advantageously prevents the overall degradation of polymer-based devices or products due to UV radiation. Polymer-based devices or products will be able to be used for a longer time without cracking, discoloration, fogging, leakage and / or complete failure.

[0092] Metallic nanoparticles incorporated into medical devices can also inactivate or kill microorganisms, preventing microorganisms from accumulating on or within the medical device. For example, the antimicrobial activity of the embedded nanoparticles can act to inhibit microbial growth and the formation of biofilms on implanted medical devices. This beneficially prolongs the use of the device in environments such as hospitals or clinics. This also facilitates the sterilization of the product, thereby reducing the cost of storage and sterilization steps.

[0093] Examples of medical devices that may be formed at least in part using the methods disclosed herein include, but are not limited to, gloves, catheters, wound dressings, syringes, and other drug delivery components, as well as polymeric portions of implantable devices (e.g., pacemakers, replacement joints, drug pumps, intrauterine devices (IUDs), cochlear implants, vascular access devices, polymeric portions of artificial heart valves), bone implants, bone nails, bone screws, tissue grafts, airway devices such as endotracheal tubes, catheters, arteriovenous grafts, bypass grafts, anastomotic clips, arterial closure devices, patent foramen ovale closure devices, and drug delivery balloons.

[0094] Nanoparticle-impregnated fibers may be disposed on or form any portion of the structure of such a device. Nanoparticle-impregnated fibers may be disposed on an outer surface of such a device. Additionally or alternatively, nanoparticle-impregnated fibers may be disposed on an outer surface that contacts tissue or a tissue-air interface (when the device is implanted).

[0095] Fig. 9 is a perspective view of nanoparticles embedded in an electrospun material. The embedded nanoparticles can be any of the nanoparticles described above, such as laser ablated spherical nanoparticles, laser ablated coralline nanoparticles, metal oxide nanoparticles, and / or combinations thereof.

[0096] VII. Examples

[0097] Example 1

[0098] Silver nanoparticles were suspended in 99.9% isopropanol. Inductively coupled plasma emission spectrophotometry (ICPOES) was used to verify the nanoparticle concentration. DLS was used to verify the size of the nanoparticles, which was found to be approximately 6 to 10 nm. Electron loss spectroscopy (ELS) STEM imaging confirmed the surface composition and short bond lengths.

[0099] It was found that in the concentration range of 0.5 mg / L (0.5 ppm) to 2 mg / L (2 ppm) of nanoparticles, the resistant bacteria were killed. The highest concentration that killed the resistant bacteria was found to be 8 mg / L (8 ppm). STEM imaging using a dark field camera without staining and with a 3 nm carbon coating allowed tracking of the nanoparticles inside and around the bacteria. STEM imaging combined with electron diffraction spectroscopy (EDS) provided evidence of the disruption of disulfide bonds and sites of ferredoxin.

[0100] Example 2

[0101] The antimicrobial properties of a polyethylene (PE) product embedded with silver nanoparticles were tested. Two polymers, Tecoflex FG-93A-B20 (W fiber) and Isoplast 2510 (D fiber), were provided and each was treated with silver nanoparticles. Figure 5A -C shows a STEM image of Tecoflex EG-93A-B20 thermoplastic embedded with nanoparticles. Figures 6A-6C Shown is a STEM image of Isoplast 2510 thermoplastic embedded with nanoparticles. Figure 7A-7B Silver nanoparticles embedded in a thermoplastic are shown.

[0102] Silver nanoparticles are manufactured in isopropanol at a concentration of 38 mg / L (38 ppm). The alcohol mixture is applied to polymer beads or particles. The polymer beads or particles are melted, and the final concentration in the resulting PE polymer is 6 mg / kg (6 ppm). This 6 mg / kg concentration has previously been successful in surface antibacterial tests. The extruded filaments are then embedded in the toming polymer and cut into a thickness of 80-100 nm and mounted on a 200 mesh formvar Carbon B TEM grid for imaging.

[0103] Imaging was performed on a JEOL 2800 scanning transmission electron microscope (STEM) using a dark field camera, a bright field camera, and a secondary surface camera. Triangulation and net counting accuracy were achieved using dual EDS detectors with a resolution of 1 nm. 2 Elemental mapping to identify nanoparticles and microparticles.

[0104] Tecoflex FG-93A-B20 thermoplastic is light purple and requires clamping or cooling stage after melt extrusion at 230℃. Figure 5A -C, under STEM, large solid metal particles with a size of hundreds of nanometers were observed. EDS mapping confirmed that these particles were barium sulfate.

[0105] The silver nanoparticles interacted directly with the sulfur chemistry and the large amount of barium sulfate (used as a filler and hardener in Tecoflex FG-93A-B20) appeared to have sequestered the silver nanoparticles. No direct nanoparticles were found on any of the grids imaged by STEM. Background silver was detected in the barium sulfate particles. Thermal dissociation was observed on the surface of the filaments, which was expected due to the lack of thermal control in the final filament formation.

[0106] Isoplast 2510 thermoplastic is dark purple and has a surface finish that is more like glass. Isoplast 2510 thermoplastic melts at 230°C and cools at room temperature (22.5°C). This thermoplastic uses phosphates (rather than barium sulfate) as fillers and hardeners. Figures 6A-6C As shown, phosphates do not interact with Ag nanoparticles and the presence of silver nanoparticles is easily found and elementally mapped. Isoplast 2510 is a more suitable candidate material to evenly distribute silver nanoparticles in the plastic. There is no same type of thermal dissociation on the surface.

[0107] Example 3

[0108] The surface antimicrobial test was performed using the standard peni-cylinder method. A conventional peni-cylinder has an outer diameter of 7.8 mm, an inner diameter of 5.8 mm, and a length of 9.9 mm. The surface area can be calculated as follows:

[0109] A s = (external surface area) + (internal surface area) + 2 (end surface area)

[0110] A s =242.6mm 2 +180.4mm 2 +42mm 2

[0111] A s =465mm 2

[0112] Because the peni-cylinder has a 45° taper at the end, the total surface area is slightly less than calculated, but the difference is insignificant.

[0113] A 20 mm long peni-cylinder-like filament was used for the antibacterial test. The diameter of the filament was 1.2 mm, with 7.5 mm of 2 The surface area and 2.3mm 2 The total surface area of ​​the 20 mm long filament is A. f =152.3mm 2 The total number of 20 mm long filaments required to represent one peni-cylinder is:

[0114] A s / A f =465 / 152.3=3.1

[0115] Three filaments were used in each test sample set to approximate the surface area of ​​one peni-cylinder surface. Metal nanoparticles were suspended in each filament.

[0116] The filaments were cut with a straight-edge disposable razor cleaned with 70% or higher concentrations of isopropanol. The filaments were measured on a continuous surface with two marks 20 mm apart and cut to length. The cut filaments were transferred to a 50 mL sample tube containing 25 mL of isopropanol and vortexed for 1 minute. The filaments were then transferred to a 50 mL sample holding container using flame / heat sterilized tweezers.

[0117] Use 10 5 , 10 6 and 10 7 Antimicrobial testing was performed against E. coli at the level of colony forming units (CFU). Three filaments per group were introduced into E. coli in tryptic soy broth and exposed to E. coli for 1 hour. Two sample groups (three filaments per group) were used for each E. coli concentration.

[0118] Remove the filament from the Tryptic Soy Broth containing the E. coli colonies and allow it to drip until the filament is free of liquid. The fiber is then introduced to purple Dey-Engley (DE) broth. If any E. coli grows from the filament that was transferred to the DE broth, the color of the broth will change to yellow.

[0119] Samples of DE broth were plated on tryptic soy agar plates to allow any colonies to grow and were mixed with the 10 5 , 10 6 and 10 7 The CFU of E. coli was compared with that of the culture. Colony counts were then performed after 24 and 48 hours of growth. The CFU of E. coli was verified by agar counts: 10 5 =23CFU; 10 6 =256 CFU; and 10 7 =1000CFU.

[0120] After 24 hours of testing, there were no CFU on any of the filament agar plates for all prepared E. coli concentrations. After 48 hours of testing, there were no CFU on any of the filament agar plates for all prepared E. coli concentrations. DE broth showed no color change for all prepared E. coli concentrations exposed to filaments after 24 and 48 hours. 5 , 10 6 and 10 7 There were no live bacteria on the surface of any of the filaments at 1 hour. Repeated tests showed the same results.

[0121] Example 4

[0122] Spherical silver nanoparticles (with no external bond angles or edges) prepared by laser ablation, which are non-ionic and do not release silver ions, were tested to determine whether they induce silver nanoparticle-resistant bacteria. No such resistance was detected after 28 generations.

[0123] Two different types of spherical silver nanoparticles were tested: Silver lot # Desktop Laser: Ag200917-104 (19 ppm) and Silver lot # Industrial Laser: 171229-101 (16.8 ppm). The spherical silver nanoparticles produced using the desktop laser had an average diameter of 8-10 nm, and the spherical silver nanoparticles produced using the industrial laser had an average diameter of 8-12 nm.

[0124] The steps of the study are outlined below:

[0125] Bacteria preparation:

[0126] 1. Spread the bacteria on Tryptic Soy Agar (TSA) plates and incubate overnight at 37°C.

[0127] 2. The next day, inoculate 10 mL of silver with Mueller Hinton broth mixed with one bacterial colony.

[0128] a. Desktop laser:

[0129] i. E. coli - Mix 4.75 ppm of silver nanoparticles in broth (2.5 mL Ag + 7.5 mL broth).

[0130] ii. Pseudomonas aeruginosa—4.75 ppm of silver nanoparticles were mixed in broth (2.5 mL Ag + 7.5 mL broth).

[0131] b. Industrial lasers:

[0132] i. E. coli - Mix 2 ppm of silver nanoparticles in broth (1.2 mL Ag + 8.8 mL broth).

[0133] ii. Pseudomonas aeruginosa—2 ppm of silver nanoparticles were mixed in broth (1.2 mL Ag + 8.8 mL broth).

[0134] 3. Incubate at 37°C and 250 RPM for 24-36 hours.

[0135] 4. Monitor growth the next day.

[0136] 5. Use an inoculating loop to serially subculture in new silver broth mixture.

[0137] 6. Every 5-7 days, streak a circle of the culture on a TSA plate to preserve the subculture, and then perform MIC test on the colonies to measure whether the bacteria have developed resistance to the spherical silver nanoparticles.

[0138] The results of the study are as follows:

[0139] MIC value:

[0140] E. coli - Industrial Laser Sample: MIC remained at 2 ppm until 28 serial passages.

[0141] DT laser samples: The culture stopped reproducing after passage 21. The MIC remained at the value in the previous passages.

[0142] P. aeruginosa - Industrial Laser Sample: MIC remained at 2 ppm until 28 serial passages.

[0143] DT laser samples: The culture stopped reproducing after passage 21. The MIC remained at the value in the previous passages.

[0144] All negative and positive control groups passed.

[0145] VIII. Additional Terms and Definitions

[0146] While certain embodiments of the present disclosure have been described in detail with reference to specific configurations, parameters, components, elements, etc., these descriptions are illustrative and should not be construed as limiting the scope of the claimed invention.

[0147] Furthermore, it should be understood that for any given component element of the described embodiments, any possible alternatives listed for that element or component can generally be used alone or in combination with each other unless otherwise implied or explicitly stated.

[0148] In addition, the numbers used in the specification and claims to represent quantities, components, distances or other measurements should be understood to be optionally modified by the term "about". When the terms "about", "approximately", "substantially", etc. are used in conjunction with a stated amount, value or condition, they can be understood to mean an amount, value or condition that deviates from the stated amount, value or condition by less than 20%, less than 10%, less than 5%, less than 1%, less than 0.1% or less than 0.01%. Optionally, the numbers can be modified by the explicit use of the term "exactly" to clarify specific circumstances where the term "about" does not apply.

[0149] Any headings and sub-headings used herein are for organizational purposes only and are not meant to limit the scope of the description or the claims.

[0150] It will also be noted that, as used in this specification and the appended claims, the singular forms "a", "an", and "the" do not exclude plural referents unless the context clearly indicates otherwise. Thus, for example, an embodiment referring to a singular object (e.g., "a medical device") may also include two or more such objects.

[0151] The embodiments disclosed herein should be understood to include / comprise the disclosed components, and therefore may include additional components that are not specifically described. Optionally, the embodiments disclosed herein are substantially free of or completely free of components that are not specifically described. That is, undisclosed components may optionally be completely omitted or substantially omitted from the disclosed embodiments. For example, undisclosed nanoparticle conjugates or undisclosed solvents may optionally be completely omitted or substantially omitted from the polymer compositions and / or finished medical products disclosed herein.

[0152] Embodiments that "substantially omit" or "substantially contain" a component may include trace and / or non-functional amounts of the component. For example, the "substantially omitted" component may include an amount of no more than 2.5%, no more than 1%, no more than 0.1%, or no more than 0.01%, based on the total weight of the composition. The same applies to other negative modifier phrases, such as, but not limited to, "substantially omitted," "substantially free," similar phrases using "substantially" or other synonyms of "essentially," and the like.

[0153] A composition that "completely omits" or is "completely free of" a component does not include a detectable amount of the component (i.e., does not include an amount above any inherent background signal associated with the testing instrument) when analyzed using standard coating composition analysis techniques, such as chromatographic techniques (e.g., thin layer chromatography (TLC), gas chromatography (GC), liquid chromatography (LC)) or spectroscopic techniques (e.g., Fourier transform infrared (FTIR) spectroscopy).

[0154] It should also be understood that the embodiments described herein may also include the properties and / or features (e.g., ingredients, components, members, elements, parts and / or portions) described in one or more separate embodiments, and are not necessarily strictly limited to the features explicitly described for that particular embodiment. Therefore, the various features of a given embodiment may be combined with other embodiments of the present disclosure and / or incorporated into other embodiments of the present disclosure. Therefore, the disclosure of certain features relative to a particular embodiment of the present disclosure should not be interpreted as limiting the application or inclusion of the features to a particular embodiment. On the contrary, it should be understood that other embodiments may also include such features.

Claims

1. A method for producing polymer fibers using a fiber spinning process, the method comprising: providing or mixing a polymer solution or a polymer melt to or with the metal nanoparticles, the metal nanoparticles comprising non-ionic metal nanoparticles formed by laser ablation; stretching the polymer solution or polymer melt into polymer fibers, whereby the polymer solution or polymer melt forms polymer fibers having metal nanoparticles incorporated therein; as well as The polymer fibers are collected on a collector.

2. The method of claim 1, wherein drawing the polymer solution or polymer melt into fibers comprises an electrospinning process.

3. The method of claim 1 or 2, wherein drawing the polymer solution or polymer melt into fibers comprises a wet spinning process.

4. The method according to any one of claims 1 to 3, wherein the metal nanoparticles comprise silver nanoparticles.

5. The method according to any one of claims 1 to 4, wherein the metal nanoparticles comprise gold nanoparticles.

6. The method according to any one of claims 1 to 5, wherein the polymer fiber comprises one or more polymers selected from the group consisting of silicone, polysiloxane, epoxy resin, polystyrene (PS), polyethylene (PE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), high density polyethylene (HDPE), polypropylene (PP), ethylene-vinyl acetate copolymer (EVA), polycarbonate (PC), polyurethane (PU), polyetheretherketone (PEEK), polylactic acid (PLA), polyhydroxyalkanoate (PHA), polyester (PES), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), polybutylene terephthalate (PBT), phenolic resin (PF), nylon / polyimide (PA), melamine formaldehyde (MF), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), polyvinyl pyrrolidone (PVP), acrylonitrile butadiene styrene (ABS), styrene block copolymer (SBC), rubber latex, nitrile, medical grade thermoplastic elastomer (TPE) and aramid.

7. The method according to any one of claims 1 to 6, wherein the metal nanoparticles comprise spherical nanoparticles. The method according to claim 7 , wherein the metal nanoparticles have an average diameter of 1 nm to 40 nm.

9. The method of any one of claims 1 to 8, wherein the nanoparticles have a particle size distribution wherein at least 99% of the metal nanoparticles have a particle size within 30% of a mean diameter, and / or wherein at least 99% of the spherical nanoparticles have a diameter within ±3 nm of a mean diameter.

10. The method of any one of claims 1 to 9, wherein the nanoparticles have a zeta potential of at least about ±10 mV (absolute value).

11. The method of any one of claims 1 to 10, wherein the metal nanoparticles comprise coralline-shaped nanoparticles.

12. The method of any one of claims 1 to 11, wherein the polymer solution or polymer melt comprises the metal nanoparticles at a concentration of about 50 ppb to about 100 ppm after mixing.

13. The method of any one of claims 1 to 12, further comprising manufacturing a medical device comprising the polymer fiber.

14. A polymer fiber product formed by the method of any one of claims 1 to 13.

15. The polymer fiber product of claim 14, wherein the polymer fiber comprises 0.5 mg / kg to about 8 mg / kg of metal nanoparticles.

16. A method of making a polymer fiber using a fiber spinning process, the method comprising: providing or mixing a polymer solution or a polymer melt with metal nanoparticles, the metal nanoparticles comprising nonionic silver nanoparticles formed by laser ablation, wherein the silver nanoparticles are spherical and have an average diameter of 1 nm to 40 nm, wherein the polymer solution or polymer melt contains the metal nanoparticles at a concentration of about 50 ppb to about 100 ppm after mixing; stretching the polymer solution or polymer melt into polymer fibers, whereby the polymer solution or polymer melt forms polymer fibers having metal nanoparticles incorporated therein; as well as The polymer fibers are collected on a collector.

17. The method of claim 16, wherein drawing the polymer solution or polymer melt into fibers comprises an electrospinning process.

18. The method of claim 16 or 17, wherein drawing the polymer solution or polymer melt into fibers comprises a wet spinning process.

19. A polymer fiber product formed by the method of any one of claims 16 to 18.

20. The polymer fiber product of claim 19, wherein the polymer fiber comprises silver nanoparticles at a concentration of about 0.5 mg / kg to about 8 mg / kg.

Citation Information

Patent Citations

  • Method and apparatus for production of uniformly sized nanoparticles

    US10137503B2

  • Method and apparatus for production of uniformly sized nanoparticles

    US10610934B2

  • 3D printing composition with light scattering nanoparticles to assist curing

    US20230133966A1

  • Composition containing spherical and coral-shaped nanoparticles and method of making same

    US9434006B2

  • Method and apparatus for production of uniformly sized nanoparticles

    US9849512B2